1998
DOI: 10.1164/ajrccm.157.4.9708058
|View full text |Cite
|
Sign up to set email alerts
|

Movement of Tuberculosis Patients and the Failure to Complete Antituberculosis Treatment

Abstract: The outcomes of tuberculosis (TB) patients who move before completing antituberculosis treatment have not been described. We studied a population-based cohort of 2,576 adult patients reported as having TB in California during 1993, including 147 patients who moved from one local health jurisdiction to another within California. We determined treatment outcomes (completed, defaulted, died, other) for 131 (89%) of these 147 patients. Patients who moved defaulted more often (relative risk [RR] = 5.5, 95% confiden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 12 publications
2
35
0
2
Order By: Relevance
“…Although not all of the patients reported as having moved away may have defaulted, the risk of defaulting is likely to be high in this group [20]. Although the level of defaulting may have been somewhat overestimated by this approach, the inclusion or exclusion of this group made little difference in the analysis of most risk factors.…”
Section: Discussionmentioning
confidence: 90%
“…Although not all of the patients reported as having moved away may have defaulted, the risk of defaulting is likely to be high in this group [20]. Although the level of defaulting may have been somewhat overestimated by this approach, the inclusion or exclusion of this group made little difference in the analysis of most risk factors.…”
Section: Discussionmentioning
confidence: 90%
“…In turn, other studies of HIV patients in the United States have shown that providing housing assistance to individuals enhances their entry and access to care (Conover & Whetten-Goldstein, 2002, Conviser & Pounds, 2002, Messeri, Abramson, Aidala, Lee, & Lee, 2002. Beyond the realm of HIV, housing instability and homelessness has been linked to default on treatment for tuberculosis (Cummings, Mohle-Boetani, Royce, & Chin, 1998), dropping out of drug treatment (Marrero et al, 2005), and nonadherence to mental health treatment referrals (Dobscha, Delucchi, & Young, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…These results are consistent with findings showing that patients who move are less likely to complete treatment. 22 Our analysis reveals potential limitations in assessing treatment outcomes using surveillance data, and highlights the need for better coordination of care between correctional facilities, state and local health jurisdictions, and international TB partners, especially upon parole.…”
Section: Discussionmentioning
confidence: 92%